Early information needs of adolescents and young adults about late effects of cancer treatment. Issue 14 (4th May 2020) - Greenzang, Katie A.; Fasciano, Karen M.; Block, Susan D.; Mack, Jennifer W.
Abstract : Background: Adolescent and young adult (AYA) cancer survivors have high risks of late effects. Little is known about the late‐effect information needs of AYAs early in treatment or their role in treatment decision making. This study evaluated the importance, quality, and implications of information about late effects in AYAs recently diagnosed with cancer. Methods: This study surveyed 201 AYAs with cancer who were 15 to 29 years old and were treated at the Dana‐Farber Cancer Institute (Boston, Massachusetts). Patients were approached within 6 weeks of their diagnosis and were asked about their late‐effect and infertility information needs, treatment decision making, and communication outcomes. Results: Forty‐five percent of the participants were female; 88% were white. Most AYAs (87% [173 of 200]) considered information about the risks of late effects to be extremely or very important; 80% (159 of 200) valued information about infertility. Many were distressed by information about late effects (53% [105 of 200]) and infertility (45% [89 of 200]); those who considered late‐effect information distressing were more likely to value this information ( P < .0001). Consideration of late effects (41% [82 of 201]) and infertility (36% [72 of 201]) greatly influenced many patients' treatment decision making. Although 92% of the patients (184 of 199) reported receiving high‐quality information about the diagnosis, 57% (113 of 199; P < .0001) and 65% (130 of 199; P < .0001) felt that they had received high‐quality information about late effects and infertility, respectively. Conclusions: Most AYAs with cancer value early information about the risks of late effects and infertility, yet many patients felt that they had not received high‐quality information about these topics. The development of age‐appropriate late‐effect communication strategies that recognize high AYA distress may help to address the gap between desired information and perceived information quality. Abstract : Most adolescents and young adults with cancer in the current study value early information about risks of late effects and infertility, in part because they find it important to their treatment decision making. However, many patients are distressed by information about the long‐term risks of cancer treatment and report receiving suboptimal information about these topics.